2019
DOI: 10.14715/cmb/2019.65.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of priming on seed germination, seedling growth and gene expression in common vetch under salinity stress

Abstract: Salinity is one of the most important abiotic stress factors that is expanding its influence because of global climate change and global warming. It causes gene expression changes, a reduction in seed germination and related characteristics, and poor seedling establishment in many crop plants by creating a lower osmotic potential in the seedbed and/or toxic ion effects in germinated seeds. In recent years, seed priming has been considered a promising strategy in modern stress management to protect plants again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Similarly, Abraha et al [ 42 ] showed that seed priming with 5g/L NaCl significantly improved early seedling growth under salt stress in maize. Likewise, seed priming with PEG-6000 alleviated the adverse effects of salt stress on seed germination and early seedling growth in common vetch [ 43 ]. Seed priming with distilled water increased the germination index, root and shoot length, and dry weight and promoted the germination and normal seedling growth of maize under salt stress [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Abraha et al [ 42 ] showed that seed priming with 5g/L NaCl significantly improved early seedling growth under salt stress in maize. Likewise, seed priming with PEG-6000 alleviated the adverse effects of salt stress on seed germination and early seedling growth in common vetch [ 43 ]. Seed priming with distilled water increased the germination index, root and shoot length, and dry weight and promoted the germination and normal seedling growth of maize under salt stress [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is sufficient evidence that priming induces seeds to absorb more water and helps in increasing percent emergence (Atak et al, 2006;Kaya et al, 2006). The reason behind the negative impact of salt stress on seedling emergence is accredited to the physiological drought it creates or the ion toxicity on the germinated seeds (Aydinoglu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The previous studies on wheat (Afzal et al, 2005;Abbas et al, 2018;Ehtaiwesh and Almajdor, 2021), canola (Hassanpoughdam et al, 2009;Heshmat et al, 2011;Aboutalebian et al, 2012;Zhu et al, 2021), Calendula officinalis (Sedghi et al, 2010), alfaafa (Jorjandi & Sirchi, 2012), Calotropis procera (Taghvaei et al, 2012), soyabean (Ahmadvand et al, 2012), Aeluropus (Nejad et al, 2013), cumin (Shoor et al, 2014, maize (Akter et al, 2018;Shah et al, 2021), Vicia (Aydinoglu et al, 2019), Camilina (Huang et al, 2021) and hargel (Salih et al, 2022) have confirmed stimulatory effects of pre-soaking amendments on plumule lengths under salt stress which fully support our findings. However, some workers have reported a decrease in the plumule growth of plants like wheat (Akbarimoghaddam et al, 2011;Biabani et al, 2013;Khan et al, 2018) and canola (Bybordi and Tabatabaei, 2009;Mohammadi et al, 2010) 1.5787 a Alpha = 0.05 %.…”
Section: Influence On Plumule Growth (Cm)mentioning
confidence: 99%
See 1 more Smart Citation
“…When common vetch seedlings were grown under salinity stress conditions, their height and root length decreased; moreover, the seedlings died when subjected to the greatest level of salinity, and the shoot dry weight, leaf number, and leaf area per seedling decreased up to 80%, 61%, and 89%, respectively [ 27 ]. The germination percentage of common vetch seeds and seedling growth also decreased in response to high salinity [ 28 ]. Previous studies in common vetch have focused primarily on the characterization and evaluation of the physiological mechanisms that occur in response to salinity stress; however, the detailed mechanism underlying the response to salinity stress of this important legume forage species at the molecular level have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%